Evaluation and study of mebendazole polymorphs present in raw materials and tablets available in the Brazilian pharmaceutical market - Aline Quelian Penna Garbuio, Tássia Hanashiro, Blanca Elena Ortega Markman, Fernando Luiz Affonso Fonseca , , Fábio Ferreira Perazzo, Paulo Cesar Pires Rosa (Journal of Applied Pharmaceutical Science, 2014)
The dissolution of a drug can be compromised by the presence of different polymorphs, which may have different solubilities. Importantly, the pharmacopoeiamonographs,usually not have tests for the characterization of these polymorphic forms of a drug. Was performed a study of polymorphic forms of mebendazole present in raw materials and also pills available in the Brazilian pharmaceutical market through the techniques of infrared (FTIR), differential scanning calorimetry (DSC), dissolution , solubility and X-ray diffraction pattern (XRPD). Through the analysis of FTIR and DSC curves showed that there are three main polymorphic forms of mebendazole present in raw materials and tablets that compound. The data obtained in the dissolution and solubility tests showed that Form A is less soluble than Form B which is less soluble than the C form, when using a dissolution medium without added surfactant. It has been found that in some tablets mebendazole there is a mixture of polymorphic forms, and that the raw materials present two major polymorphic forms. Then it is suggested the need of quality control regarding the type of polymorph used in the production of mebendazole tablets to ensure greater therapeutic efficacy.
Keywords: Mebendazole,Polymorphism,Infrared,Dissolution,Differential Scanning Calorimetry